If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (9 + u)(6u + 4) = 0 Reorder the terms: (9 + u)(4 + 6u) = 0 Multiply (9 + u) * (4 + 6u) (9(4 + 6u) + u(4 + 6u)) = 0 ((4 * 9 + 6u * 9) + u(4 + 6u)) = 0 ((36 + 54u) + u(4 + 6u)) = 0 (36 + 54u + (4 * u + 6u * u)) = 0 (36 + 54u + (4u + 6u2)) = 0 Combine like terms: 54u + 4u = 58u (36 + 58u + 6u2) = 0 Solving 36 + 58u + 6u2 = 0 Solving for variable 'u'. Factor out the Greatest Common Factor (GCF), '2'. 2(18 + 29u + 3u2) = 0 Factor a trinomial. 2((9 + u)(2 + 3u)) = 0 Ignore the factor 2.Subproblem 1
Set the factor '(9 + u)' equal to zero and attempt to solve: Simplifying 9 + u = 0 Solving 9 + u = 0 Move all terms containing u to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + u = 0 + -9 Combine like terms: 9 + -9 = 0 0 + u = 0 + -9 u = 0 + -9 Combine like terms: 0 + -9 = -9 u = -9 Simplifying u = -9Subproblem 2
Set the factor '(2 + 3u)' equal to zero and attempt to solve: Simplifying 2 + 3u = 0 Solving 2 + 3u = 0 Move all terms containing u to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + 3u = 0 + -2 Combine like terms: 2 + -2 = 0 0 + 3u = 0 + -2 3u = 0 + -2 Combine like terms: 0 + -2 = -2 3u = -2 Divide each side by '3'. u = -0.6666666667 Simplifying u = -0.6666666667Solution
u = {-9, -0.6666666667}
| 5(x+3)-(-3x-5)= | | x(x-32)=8025 | | x-32=68 | | -9y-5=8y+1 | | x(x-15)=7600 | | x(x-15)=5950 | | 1328400=0.5*9840*x^2 | | 0.21y-2.2=0.11y+1-0.7y | | (5x-4)squared= | | 4x(9x-7y)= | | 8z-25=-25+6z | | X-3=1.2 | | 7x-(3x+5)-8=(1/2)(8x+20)-7x+5 | | 10x=-8 | | X+3=1.2 | | 8x+3=6x+43 | | 3y^2-4y+21=0 | | 3y^2-4x+21=0 | | x(x-7)=1100 | | x(x-7)=1150 | | -7x-1.7=-9x-0.6 | | 4(9x-7)= | | x-7=750 | | 9x+7y-3x+2y= | | 4x+3=x+3.3 | | x^7=12 | | 15000+0.1x=25000+0.05x | | 2.6y=8.8 | | -(x-7)+(5/3)=2(x+9) | | -(x-7)+(53)=2(x+9) | | 3600/2800 | | 2800/3600 |